Exploring the Relationship Between Hypertension and Cerebral Microvascular Disease - Vasiliki Katsi; Andreas Mavroudis; Ioannis Liatakis; Manousiadis Konstantinos; Konstantinos Tsioufis (Diseases)
Background/Objectives: Hypertension exerts negative effects on the vasculature representing a key risk factor for cardiovascular disorders, cerebral and Cerebral Small Vessel Disease (CSVD). Methods: An extensive research in the literature was implemented in order to elucidate the role of hypertension in the pathogenesis of CSVD. Results: Hypertension-mediated vascular dysfunction and chronic cerebral hypoperfusion are closely linked to CSVD. CSVD encompasses a wide range of lesions depicted on brain Magnetic Resonance Imaging (MRI) or Computed Tomography (CT) scans. The presenting symptoms and clinical course are highly variable, as a significant proportion of patients remain asymptomatic. Nevertheless, CSVD is associated with an increased risk of stroke, dementia and mobility disorders. Various randomised controlled trials have been implemented trying to shed light on the effect of vascular risk-modifying agents and lifestyle interventions on the prevention and treatment of small vessel disease. Conclusions: Hypertension has a pivotal role in the pathogenesis of CSVD. However, further research is required for a better understanding of the relationship between blood pressure levels and CSVD progression.